Growth-Trade-Environment Nexus in India - Pradyot Ranjan Jena; Ulrike Grote (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
This paper evaluates the environmental impacts of economic growth and trade liberalization in India. The empirical strategy in this paper is to estimate the scale, technique and trade-induced composition effects of trade liberalization on pollution. We collect data across major industrial states of India over the time period 1991-2003 and use panel regression techniques for such estimation. The results establish that the impact of growth and trade liberalization on environmental pollution is not unique across the pollutants. It rather depends upon the specific indicator that is examined. Finally, we conclude that trade promotion in the presence of a dynamic pollution regulatory framework can yield sustainable trade.
Keywords: Q53; Q56; Q58; 330; Trade and Environment; Pollution regulation index; Air pollution; Government policy